What Matters and What Matters Most for Survival After age 80? A Multidisciplinary Exploration Based on Twin Data - Johansson, Boo; Thorvaldsson, Valgeir (Frontiers in Psychology, 2021)
We addressed the questions of what matters and what matters most for subsequent survival past age 80. The data was drawn from the Swedish OCTO Twin Study, with a sample (N=699) consisting of identical and same-sex fraternal twin pairs, followed from age 80 until death. Information concerning age of death was obtained from the population census register. We estimated heritability using an ACE model and evaluated the role of multiple predictors for the mortality-related hazard rate using Cox regression. Our findings confirmed a low heritability of 12 %. As expected, longer survival was associated with being a female, an apolipoprotein E (APOE) e4 allele non-carrier, and a non-smoker. The opposite was the case for several diseases found to be associated with shorter survival (cerebrovascular, dementia, Parkinson´s, and diabetes) and health conditions (high diastolic blood pressure, low body mass index, and hip fracture). Stronger grip and better lung function, as well as better vision (but not hearing), and better cognitive function (self-evaluated and measured) was related to longer survival. Social embeddedness, better self-evaluated health, and life-satisfaction were also significantly related to longer survival. After controlling for the impact of comorbidity, functional markers, and personality-related predictors, we found that cerebrovascular diseases, compromised cognitive functioning, self-related health, and life-satisfaction remained as strong predictors. Cancer was only associated with the mortality hazard when accounting for co-morbidity. The survival estimates were mostly in an anticipated direction and contained effect sizes within the expected range. Noteworthy, we found that some of the so-called “soft-markers” remained strong predictors, despite a control for other factors. This implies that self-evaluation of health and life-satisfaction provide additional and valuable information concerning whether individuals feel well and find it worth living, which in fact increase the likelihood for subsequent survival into very old age.